2023
DOI: 10.3389/fimmu.2023.1219929
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic nutritional index as a prognostic biomarker for gastrointestinal cancer patients treated with immune checkpoint inhibitors

Abstract: ObjectiveOur study represents the first meta-analysis conducted to evaluate the prognostic utility of the baseline prognostic nutritional index (PNI) in patients with gastrointestinal cancer (GIC) who received immune checkpoint inhibitor (ICI) therapy.MethodsWe searched PubMed, the Cochrane Library, EMBASE, and Google Scholar until April 23, 2023, to obtain relevant articles for this study. Our analysis examined several clinical outcomes, including overall survival (OS), progression-free survival (PFS), object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The results demonstrated that the PNI exhibited higher prognostic value in all subgroup analyses [ 26 ]. Zhang and his colleagues’ meta-analysis further corroborated these findings, integrating data and results from 17 studies, revealing that the PNI is a reliable predictive factor for gastric cancer patients receiving ICIs [ 27 ]. Meanwhile, Wan and colleagues have extensively studied inflammatory markers and found that the NLR was associated with the benefits of immunotherapy [ 28 ].…”
Section: Discussionmentioning
confidence: 81%
“…The results demonstrated that the PNI exhibited higher prognostic value in all subgroup analyses [ 26 ]. Zhang and his colleagues’ meta-analysis further corroborated these findings, integrating data and results from 17 studies, revealing that the PNI is a reliable predictive factor for gastric cancer patients receiving ICIs [ 27 ]. Meanwhile, Wan and colleagues have extensively studied inflammatory markers and found that the NLR was associated with the benefits of immunotherapy [ 28 ].…”
Section: Discussionmentioning
confidence: 81%
“…p < 0.1 and I 2 > 50% were defined as high heterogeneity and a random effect model would be applied when it occurred. Otherwise, the fixed effect model was used [20]. The tests of Egger [21] and Begg [22] were employed to evaluate publication bias.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity was estimated using Cochran’s Q test and I 2 statistics. A fixed-effect model with the Inverse Variance method was utilized when p > 0.1 and I 2 <50% indicated non-significant heterogeneity; otherwise, the random-effect model with the DerSimonian-Laird method was applied [ 17 , 18 ]. To investigate publication bias, the funnel plot, Egger tests, and Begg tests were utilized [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%